"If You're Not at the Table, You're on the Menu": Learning to Participate in Policy Advocacy as a Teacher Educator. (3rd April 2022) - Aydarova, Elena; Rigney, James; Dana, Nancy Fichtman
ABSTRACT: Scholars have long urged teacher educators to engage in policy advocacy and to respond to mounting attacks on the teacher education field. Prior research has shown that teacher educators feel largely unprepared to participate in policy debates. This observation raises the question of how those who do engage in advocacy learn to navigate the contested terrain of teacher education policy. Drawing on a multiple case study research project, we argue that learning policy advocacy is a prolonged process, during which participants acquire the language used by policymakers and learn the procedures utilized by policymaking communities. This learning entails peripheral participation in policy processes, modeling, and mentoring. Our study sheds light on the importance of professional networks and relationships as support systems to expand teacher educators' ability to participate in policy advocacy and reclaim their professional voice in policy debates.